Meeting report: 27th International conference on antiviral research, in Raleigh, NC, USA - Vere Hodge, R. Anthony (Antiviral Res, 2014)
The 27th International Conference on Antiviral Research (ICAR) was held in Raleigh, North Carolina, USA from May 12 to 16, 2014. This article summarizes the principal invited lectures. John Drach (Elion Award) described the early days of antiviral drugs and their novel modes of action. Piet Herdewijn (Holý Award) used evolutionary pressure to select DNA polymerases that accept nucleoside analogs. Replacing thymine by 5-chlorouracil led to the generation of a new form of Escherichia coli. Adrian Ray (Prusoff Award) demonstrated how prodrugs can markedly improve both the efficacy and safety of potential drugs. The keynote addresses, by David Margolis and Myron Cohen, tackled two emerging areas of HIV research, to find an HIV “cure” and to prevent HIV transmission, respectively. These topics were discussed further in other presentations – a cure seems to be a distant prospect but there are exciting developments for reducing HIV transmission. TDF-containing vaginal rings and GSK-744, as a long-lasting injection, offer great hope. There were three mini-symposia. Although therapy with TDF/FTC gives excellent control of HBV replication, there are only a few patients who achieve a functional cure. Myrcludex, an entry inhibitor, is active against both HBV and HDV. The recent progress with HBV replication in cell cultures has transformed the search for new antiviral compounds. The HBV capsid protein has been recognized as key player in HBV DNA synthesis. Unexpectedly, compounds which enhance capsid formation, markedly reduce HBV DNA synthesis. The development of BCX4430, which is active against Marburg and Ebola viruses, is of great current interest.